AN ASSESSMENT OF THE MICROBIOLOGICAL QUALITY OF ANTI-VIRAL CHURNA SOLD IN INDIA BY AYURVEDIC MEDICAL PRACTITIONERS - KAZI, SARFARAZ; Bais, Sanjay (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives behind of this study are to analyze the unregistered herbal products dispensed by Ayurvedic practitioners, as per the WHO guidelines for determination of potentially hazardous contaminants. To aware the registered medical practitioners regarding contamination of herbal product, the patients are using unregistered herbal products from registered medical practitioners. Methods: The method employed in this study was a pour plate method. The specific media plates were incubated for 24 h at 37°C. On a colony counter, the plate was placed and observed for the presence of micro-organisms. The media used were nutrient agar medium and cetrimide nutrients, agar, saline agar, and MacConkey agar. Result: The present study found microbial contamination in herbal products that are widely available across the country. The formulations coded AV5, AV6, and AV7 were found to be contaminated by Pseudomonas aeruginosa and AV5 and AV6 were found to be contaminated by Escherichia coli, whereas the formulations coded AV1 and AV2 were found to be contaminated by Staphylococcus aureus in above permissible limit, posing a risk of infection if consumed. Conclusion: According to the findings of this study, it shows that few herbal formulations were showing the presence of micro-organism above the permissible of given by the WHO.